2020
DOI: 10.1177/0954410020904555
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning-based inertia tensor identification of the combined spacecraft

Abstract: The identification accuracy of inertia tensor of combined spacecraft, which is composed by a servicing spacecraft and a captured target, could be easily affected by the measurement noise of angular rate. Due to frequently changing operating environments of combined spacecraft in space, the measurement noise of angular rate can be very complex. In this paper, an inertia tensor identification approach based on deep learning method is proposed to improve the ability of identifying inertia tensor of combined space… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…The angular rates and control torques of combined spacecraft are set as the input of a deep neural network model, and conversely, the inertia tensor is then set as the output. Training the MLP model refers to the process of extracting a higher abstract feature, i.e., the inertia tensor [36,37]. Another approach to solve the parametric reconstruction is to use a recurrent neural network.…”
Section: System Identification Through Reconstruction Of Parametersmentioning
confidence: 99%
“…The angular rates and control torques of combined spacecraft are set as the input of a deep neural network model, and conversely, the inertia tensor is then set as the output. Training the MLP model refers to the process of extracting a higher abstract feature, i.e., the inertia tensor [36,37]. Another approach to solve the parametric reconstruction is to use a recurrent neural network.…”
Section: System Identification Through Reconstruction Of Parametersmentioning
confidence: 99%
“…12 As the internal calculation of DNN involves simple matrix multiplications, control values are output in real time by online sensing of the current flight state, which is then input into the DNN. 13 Chai et al 14 reported an optimal trajectory planning and real-time altitude control method for a six degrees of freedom spacecraft based on DNN and proved the real-time ability and reliability of the method. Yang Shi et al 15 used a homotopy algorithm to generate a large number of state-action pairs and trained a DNN offline for online trajectory generation.…”
Section: Introductionmentioning
confidence: 98%